Implementación de la filosofía Lean en la producción de concreto con autohormigonera - Cruz-Rosales, Christopher (Instituto Tecnológico de Costa Rica, 2017)
The following investigation seeks the Lean philosophy implementation on the concrete production process with a self-propelled mixer, developing a methodology that involves Lean tools. At the beginning, the necessary requirements for the methodology were determined, advantages and disadvantages of operating with the equipment, too. Then, the information control and evaluation tools before, during, and after the concrete production process were developed. Once the control tools are settled, the concrete production process without a Lean Construction implementation was evaluated through travel diagrams, flow diagrams and value stream mapping. Also, a productivity analysis of the concrete placement process was made. A costs analysis used all the previous information and showed unbearable losses for the enterprise. With this on mind, the spotted improvements were implemented and, using Lean, there were improvements on the processes that went over a 50%, and the costs were lowered in a 30%, which made them bearable for the company. After the implementation, decision making tools for the equipment use on future projects were created.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Construcción, 2017.
Keywords: Productividad; Costos; Cemento; Concreto; Procesos; Control